Human and mouse platelet transcriptomes and proteomes for phenotyping 3474 genes with hemostatic and platelet traits - Jingnan Huang; Federico Marini; Fiorella A. Solari; Frauke Swieringa; Bas de Laat; Ilaria De Simone; Luigi Grassi; Xiang Gui; Kunpeng Li; Elizabeth A. Middleton; Neil V. Morgan; Isabella Provenzale; et al. (Blood Vessels, Thrombosis & Hemostasis)
Abstract: The hemostatic process relies on platelet and coagulation activation, with additional roles of red blood cells and the vessel wall. By systematic screening of databases for gene-linked information on hemostasis, we collected phenotypic profiles of 3474 orthologous human and mouse genes regarding bleeding, arterial thrombosis, thrombophilia, platelet traits, coagulation, and erythrocytes. Comparisons showed that defects in 252 mouse genes led to increased bleeding combined with platelet dysfunction or thrombocytopenia, in addition to 150 human orthologs that are registered for familial bleeding disorders, based on panel sequencing. Additionally, 139 mouse genes contributed to arterial thrombosis without bleeding phenotype. To further investigate the role of platelets in hemostasis, we integrated multiple genome-wide RNA-sequencing transcriptomes and proteomes from healthy subjects and C57BL/6 mice. This provided reference levels for 54 790 (54 247) transcripts and 6379 (4563) proteins in human (mouse) platelets. Orthologous transcripts in human and mouse platelets correlated with R=0.75, whereas orthologous platelet proteins correlated with R=0.87. Comparison with the phenotypic analysis revealed the following: (i) overall high qualitative similarity of human and mouse platelets regarding composition and function; (ii) presence of transcripts in platelets for most of the 3474 phenotyped genes; (iii) preponderance of syndromic platelet-expressed genes; and (iv) 20-40% overlap with genes from genome-wide association studies. For 42 mouse genes, among which receptors, signaling proteins, and transcription regulators (ASXL1, ERG, GATA2, MEIS1, NFE2, and TAL1), we confirmed novel links with human platelet function or count. This interspecies comparison can serve as a valuable resource for researchers and clinicians studying the genetics of blood-borne hemostasis and thrombosis.